A new species of fern of the genus Pteris (Filicales: Pteridaceae) endemic to Costa Rica. - Rojas Alvarado, Alexander Fco. (2006)
Abstract: A new species of fern of the genus Pteris (Filicales: Pteridaceae) endemic to Costa Rica. The new fern species Pteris herrerae A. Rojas & M. Palacios, endemic to Costa Rica, is described. It differs from P. decurrens C. Presl in basal segments reduced to 1/5-1/2 of the next segment (vs. 2/3-3/4), basal pinnae not bifurcated (vs. bifurcated), pinnae apex mucronate (vs. acuminate) and segment apex undulate (vs. dentate). It differs from Pteris consanguinea in the elliptic pinnae (vs. oblong), two segments reduced on the base (vs. lack), segments entire to undulate (vs. dentate), basal pinnae without basiscopic lobes (vs. with basiscopic lobes) and segment apex entire to undulate (vs. dentate).